Work psychology the basics - Dean, Laura; Cousans, Fran (Routledge, 2024)
"Work Psychology: The Basics provides an accessible, jargon-free introduction to the fundamental principles of work and occupational psychology. Covering key theories and models in this dynamic area, it offers a solid understanding of both academic theory and practical applications"--